2018
DOI: 10.1097/gox.0000000000001634
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Recovery after Surgery Pathway for Microvascular Breast Reconstruction Is Safe and Effective

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(132 citation statements)
references
References 39 publications
5
125
1
1
Order By: Relevance
“…Recent developments in expedited recovery after surgery protocols support this idea, as it is now becoming commonplace to offer narcotic-limiting pain control regimens that do not require inpatient intravenous administration. 28,29 As recently reported in the literature, these factors have already been paired with advanced surgical techniques, such as ribsparing exposure of the mammary vessels and microrectusfascial incisions for flap harvest, to further limit pain and expedite recovery to successfully perform microsurgical breast reconstructions in the ambulatory setting. 30 However, larger prospective studies are still needed to verify these results before these techniques are broadly adopted.…”
Section: Discussionmentioning
confidence: 98%
“…Recent developments in expedited recovery after surgery protocols support this idea, as it is now becoming commonplace to offer narcotic-limiting pain control regimens that do not require inpatient intravenous administration. 28,29 As recently reported in the literature, these factors have already been paired with advanced surgical techniques, such as ribsparing exposure of the mammary vessels and microrectusfascial incisions for flap harvest, to further limit pain and expedite recovery to successfully perform microsurgical breast reconstructions in the ambulatory setting. 30 However, larger prospective studies are still needed to verify these results before these techniques are broadly adopted.…”
Section: Discussionmentioning
confidence: 98%
“…Seven studies investigated the utilization of enhanced recovery after surgery (ERAS) pathways in providing pain control after autologous breast reconstruction. 31, [33][34][35][36][37][38][39][40] Pathways varied markedly in regard to pre, intra, and postoperative interventions. All studies demonstrated a reduction in opioid utilization with ERAS approaches.…”
Section: Enhanced Recovery Pathwaysmentioning
confidence: 99%
“…Using surgery specific protocols and checklists creates a standardized care plan which encourages patient engagement and creates a collaborative team structure. Recently, Astanehe et al 101 reported significantly decreased narcotic and antiemetic use, early regular diet tolerance and mobilization, and less hospital stay after developing an ERAS (early recovery after surgery) guideline based care protocol for microsurgery patients.…”
Section: Teamwork and Surgical Efficacymentioning
confidence: 99%